Effect of process variables on green synthesis of copper nanoparticles from solanum lycopersicum and Psidium guajava and its antibacterial activities - Muhammad, A.; Umar, Ashiru; U Birnin-Yauri, A.; Abubakar Sanni, H.; A.R, Ige; M Elinge, C. (International Journal of Advanced Chemistry, 2022)
In this study copper nanoparticles were synthesized using extracts from Solanum lycopersicum (Tomato) and Psidium guajava (Guava) fruits. The synthesis process optimized experimental conditions such as temperature, concentration of precursor and amount of fruit extract. The synthesized nanoparticles were characterized using Uv-vis, FTIR, XRD, SEM and EDX techniques. Copper nanoparticles synthesized with tomato and guava extracts had diameters of 52nm and 25nm, respectively. The antibacterial activity of the synthesized nanoparticles was tested using pathogenic bacteria; Escherichia coli and Staphylococcus aureus and their results revealed that copper nanoparticles are promising antibacterial agents. The optimum conditions for the synthesis were 0.05 M, 80 oC and 10cm3 for concentration, temperature and volume of fruit extract, respectively.Â Â Â